Iliopsoas hematoma in a patient with sickle cell disease. Issue 7 (12th March 2018) - Zielonka, Benjamin; Cohen, Alan R.; Smith‐Whitley, Kim; Doshi, Bhavya S.
Abstract: Although musculoskeletal pain in patients with sickle cell disease (SCD) is most frequently the result of vaso‐occlusive episodes, clinicians often consider other etiologies including osteomyelitis, avascular necrosis, and trauma. In this study, we report the case of a young female with SCD with hip and back pain secondary to a nontraumatic iliopsoas periosteal hematoma with evidence of adjacent bone infarction. The pathophysiology, diagnostic considerations, and management of periosteal hematomas in SCD are reviewed. This case highlights the need for recognition of unusual causes of musculoskeletal pain in SCD.